Controlled synthesis of novel one-dimensional structured ZIFs via supramolecular self-assemblies. Issue 23 (29th May 2018) - Li, Yali; Zhu, Jianhua; Cui, Mingfang; Yan, Jufen
Abstract : Various 1D ZIF-8 nanomaterials have been synthesized via the self-templates of supramolecular self-assemblies, which exhibit hierarchical pores and high surface area. The resultant microstructures could be applied as excellent drug delivery vehicles and also as excellent carriers for enzymes with remarkable enzymatic activity. Abstract : Herein, one-dimensional ZIF-8 nanomaterials, including nanofibers, nanotubes, nanobelts and thin-helical ribbons, have been demonstrated as self-templates of zinc-cholate (ZnSC) supramolecular self-assemblies. The morphology of ZnSC templates can be well-tuned by solvent ratios and transcribed into that of the resultant ZIF-8 nanomaterials. This procedure provides a versatile methodology to design and fabricate diverse 1D MOFs such as ZIF-67 and ZIF-7. The obtained ZIF-8 nanobelts exhibit hierarchical pores, including mesopores and intrinsic micropores, and high surface area and total pore volume (656 m 2 g −1 and 0.78 cm 3 g −1, respectively), which serve as excellent drug delivery vehicles. Porous nanobelts can also be applied as a carrier of horseradish peroxidase (HRP), which show both peroxidase-like activity and enhanced enzymatic activity.